BDNF Val66met and 5‐HTTLPR polymorphisms predict a human in vivo marker for brain serotonin levels. Issue 1 (13th September 2014) - Fisher, Patrick M.; Holst, Klaus K.; Adamsen, Dea; Klein, Anders Bue; Frokjaer, Vibe G.; Jensen, Peter S.; Svarer, Claus; Gillings, Nic; Baare, William F.C.; Mikkelsen, Jens D.; Knudsen, Gitte M.
Abstract Brain‐derived neurotrophic factor (BDNF) has been implicated in multiple aspects of brain function including regulation of serotonin signaling. The BDNF val66met polymorphism (rs6265) has been linked to aspects of serotonin signaling in humans but its effects are not well understood. To address this, we evaluated whether BDNF val66met was predictive of a putative marker of brain serotonin levels, serotonin 4 receptor (5‐HT4) binding assessed with [11C]SB207145 positron emission tomography, which has also been associated with the serotonin‐transporter‐linked polymorphic region (5‐HTTLPR) polymorphism. We applied a linear latent variable model (LVM) using regional 5‐HT4 binding values (neocortex, amygdala, caudate, hippocampus, and putamen) from 68 healthy humans, allowing us to explicitly model brain‐wide and region‐specific genotype effects on 5‐HT4 binding. Our data supported an LVM wherein BDNF val66met significantly predicted a LV reflecting [11C]SB207145 binding across regions (P = 0.005). BDNF val66met met‐carriers showed 2–9% higher binding relative to val/val homozygotes. In contrast, 5‐HTTLPR did not predict the LV but S‐carriers showed 7% lower neocortical binding relative to LL homozygotes (P = 7.3 × 10−6). We observed no evidence for genetic interaction. Our findings indicate that BDNF val66met significantly predicts a common regulator of brain [11C]SB207145 binding, which we hypothesize reflects brain serotonin levels. In contrast, our data indicate that 5‐HTTLPR specifically affects 5‐HT4 binding in the neocortex. These findings implicate serotonin signaling as an important molecular mediator underlying the effects of BDNF val66met and 5‐HTTLPR on behavior and related risk for neuropsychiatric illness in humans. Hum Brain Mapp, 36:313–323, 2015. © 2014 Wiley Periodicals, Inc.